Teachers Performing Professionalism - Bourke, Terri (SAGE Publishing, 2018)
Faced with the perceived need to redefine education for more economic utilitarian purposes, as well as to encourage compliance with government policies, Australia, like many other Anglophone nations, has engaged in numerous policy shifts resulting in performativity practices becoming commonplace in the educational landscape. A series of interviews with teachers from Queensland, Australia, in which they revealed their experiences of professionalism are examined archaeologically to reveal how they enact their roles in response to this performative agenda. Findings suggest that while there is some acceptance among teachers of the performative discourse, there is increasing resistance, which permits the construction of alternative or counter-discourses to the currently internationally pervasive performative climate.